الآليات الحجاجية في سورة الشعراء - موساوي, فريجات, شيماء زينب (University of El-oued, 2021)
في ما يلي ملخص بحث الآليات الحجاجية في سورة الشعراء ، وقد اشتملت هذه الدراسة على فصلين لهذا الموضوع فالفصل الأول ، نظري و كان بعنوان : الحجاج مفاهيمه وآلياته ، حيث تطرقنا فيه إلى مفهوم الحجاج في اللغة والاصطلاح ومفهومه عند العرب و الغرب قديما و حديثا و ذكرنا فيه نشأة الحجاج و تقاطع المفاهيم بينه و بين الجدل و الخطابة و البرهنة و الاستدلال وكذلك الحجاج والخطاب القرآني ، و أيضا آليات الحجاج اللغوية والبلاغية والشبه منطقية ، بينما تطرقنا في الفصل الثاني التطبيقي إلى آليات الحجاج في سورة الشعراء ، فهو عبارة عن تمهيد للسورة بذكر اسمائها ، و سبب نزولها ، و أيضا محاور السورة و فضلها كما أبرزنا آليات الحجاج اللغوية و البلاغية و الشبه منطقية المتجسدة في السورة Summary: The following is a summary of the discussion of the pilgrim mechanisms in Surat al-Shu`ara, and this study included two chapters on this subject. The first chapter is theoretical and was entitled: Pilgrims Concepts and Mechanisms, where we touched on the concept of pilgrims in language and terminology and its concept among Arabs and the West, ancient and modern, and we mentioned In it is the emergence of the pilgrims and the intersection of concepts between him and the debate, rhetoric, proof and inference, as well as the pilgrims and the Qur’anic discourse, as well as the linguistic, rhetorical and semi-logical mechanisms of the pilgrims, while in the second applied chapter we touched on the mechanisms of the pilgrims in Surat al-Shu`ara, which is a prelude to the chapter by mentioning its names , and the reason for its revelation, as well as the axes of the surah and its merit, as we have highlighted the linguistic, rhetorical and semi-logical mechanisms of al-Hajjaj embodied in the surah.
Keywords: الحجاج الخطاب القرآني